Osoba i wartości - Stróżewski, Władysław (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
The main goal of this article is to present at phenomenological reflection some relations between human being and universal values. Autor of article unites theological and philosophical aspects of human life. It’s show being’s conditio, man’s choising and acts in relation to other and to God.